Notes on the genus Leveillula (Erysiphaceae): a new unrecorded species and notes on Leveillula infecting Ficus, Cucurbita and Tropaeolum in Iran - Khodaparast, Seyed Akbar; Takamatsu, Susumu; Shadlou, Adel; Damadi, Mohsen; Pirnia, Mahdi; Jahani, Mahdi (Phytotaxa, 2016)
Taxonomy of the genus Leveillula has long been considered as a challenge in powdery mildew systematics. During the last decade the rDNA diversity has been used for phylogenetic analysis of the genus Leveillula aiming for better understanding of the genetic diversity and taxonomy of the genus. Iran with an arid and warm climate provides a high Leveillula powdery mildew diversity associated with a wide range of host plants. In this study we have obtained additional rDNA ITS sequences from four samples which show more diversity on ITS rDNA region. According to our observation morphology of Leveillula on Tropaeolum majus is different from what described as L. tropaeolicola on this host species. Leveillula on Ficus carica could be closely related to L. contractirostris. The fungus on Cucurbita is morphologically different from L. taurica, a common species that has been recorded on a wide range of crops as well as Cucurbitaceae. To determine phylogenetic relationships and to facilitate species identification, ITS regions of rDNA were sequenced for new collections. Sequence of rDNA ITS from Cucurbita powdery mildew showed 100% identity to those of L. thevenotiae. Leveillula on Ficus carica clustered with L. contractirostris. ITS sequences of L. jaczewskii was generated for the first time. These data showed that L. jaczewskii is closely related to L. taurica on Zygophyllum fabago (holotype host for L. taurica), however, the two DNA sequences differ at five positions.